1994
DOI: 10.1093/infdis/169.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prophylaxis with Pyrimethamine for Toxoplasmic Encephalitis in Patients with Advanced Human Immunodeficiency Virus Disease: Results of a Randomized Trial

Abstract: Pyrimethamine, 25 mg thrice weekly, was evaluated as primary prophylaxis for toxoplasmic encephalitis (TE) in a double-blind, randomized clinical trial in patients with human immunodeficiency virus (HIV) disease, absolute CD4 lymphocyte count of < 200/microL (or prior AIDS-defining opportunistic infection), and the presence of serum IgG to Toxoplasma gondii. Leucovorin was coadministered only for hematologic toxicity. There was a significantly higher death rate among patients receiving pyrimethamine (relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…Because the development of anemia is proportional to both concentration and time of exposure to dapsone hydroxylamine [55], slightly lower toxicity might have occurred with smaller doses of dapsone given more frequently. As the mortality rate was identical for both prophylaxis groups, data suggesting higher mortality among patients receiving prophylaxis with either dapsone [48] or pyrimethamine [56] are not supported by our study.…”
Section: Discussioncontrasting
confidence: 76%
“…Because the development of anemia is proportional to both concentration and time of exposure to dapsone hydroxylamine [55], slightly lower toxicity might have occurred with smaller doses of dapsone given more frequently. As the mortality rate was identical for both prophylaxis groups, data suggesting higher mortality among patients receiving prophylaxis with either dapsone [48] or pyrimethamine [56] are not supported by our study.…”
Section: Discussioncontrasting
confidence: 76%
“…After reintroduction, all patients were administered 1 open-label, singlestrength TMP-SMZ tablet daily for 6 months (maintenance phase). Patients missing 11 week of consecutive doses or 130 doses during the maintenance phase were declared to have treatment failure. The use of antihistamines, nonsteroidal agents, or corticosteroids was encouraged during both the reintroduction and the maintenance phases, as needed for any adverse reactions.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to providing effective prophylaxis for PCP, there is evidence that TMP-SMZ is effective as prophylaxis for toxoplasmosis and also may be useful in preventing infections caused by a variety of other organisms [7][8][9][10][11][12].…”
Section: Trimethoprim-sulfamethoxazole (Tmp-smz) Is the Most Effectivementioning
confidence: 99%
“…Therefore, treatment with pyrimethamine should be carefully considered in patients suffering from immune defects in which a worsening of clinical conditions could be determined. To this regard, it has been previously observed that human immunodeficiency virus type 1-infected patients treated with pyrimethamine as a primary prophylaxis against toxoplasmic encephalitis showed a higher mortality rate in comparison with untreated control patients (Jacobson et al, 1994).…”
Section: Mechanisms Of Pyrimethamine Apoptosis 1055mentioning
confidence: 99%